A new method to enhance the impingement/effusion cooling performance: Applying a guiding ring to the hot side. (March 2019) - Cai, Lin; Wei, Xiong; Guo, Jianghua
Impingement/effusion cooling is widely used in gas turbine combustor cooling and other industrial fields. In this paper, a new method to enhance the impingement/effusion cooling performance by applying a guiding ring to the hot side of effusion plate has been carried out. The heat transfer flow field with or without guiding ring have been calculated using computational fluid dynamics simulation. The shear stress transport k–ω model is selected for the turbulence model. The experiment data reported in the literature has been used for numerical verification. After grid independent learning, both single effusion hole and multiple effusion holes model have been investigated. The results show that, for the single-hole model, the maximum cooling effectiveness ( η ) is increased to about 0.2 when setting a guiding ring in front of the effusion hole. While for the multiple holes model, the cooling effectiveness is obviously enhanced in the region of X / d = 0–47.0. In order to analyze the mechanism of cooling enhancement, the velocity field and turbulence kinetic energy distribution have been given and discussed, including the moment ratio distribution of the multiple effusion holes model. Meanwhile, the temperature distribution of the guiding ring has been carried out. It shows that the guiding ring root zone is cooled by the impingement coolant, which makes the guiding ring surface temperature relatively low.